From Traditional to Modern Education: The Effectiveness of Quizlet as a Learning Medium to Enhance Arabic Learning Outcomes in Al-Adad wa Al-Ma'dud - Saidah, Mandrasi Amira; Matbubah, Rifaatul; Arifin, Muhammad Syamsul; Wahyudi, Muhammad (al-Ittijah: Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2026)
The process of learning Arabic at Darussalam Islamic Institution, Rajapolah, Tasikmalaya faces several linguistic and pedagogical challenges, including grammatical differences and limited innovation in learning media. One of the most complex topics is the grammatical pattern of cardinal numbers (‘Adad Ma’dūd), which involves gender agreement and structural changes, particularly in numbers 3–10. In addition, teachers still rely on traditional learning media that are less engaging, resulting in low student participation and declining learning outcomes. Therefore, more attractive, responsive, and technology-based learning media are urgent, such as Quizlet. This study aims to measure the effectiveness of using Quizlet as a learning medium on students’ Arabic learning outcomes, specifically in the topic of ‘Adad Ma’dūd, with third-grade female students as the research subjects. This research employed a quantitative experimental method using a non-equivalent control group design. Data were collected from all third-grade female students and analysed using a t-test to determine differences in learning outcomes between the experimental and control groups. The results showed a significant difference between the two groups. The average score of the experimental group was 79.06, which was higher than the control group’s average score of 72.16. Furthermore, the statistical test result showed a Sig. (2-tailed) value of 0.008 < 0.05, indicating that the use of Quizlet is effective in improving students’ learning outcomes. Based on these findings, it can be concluded that Quizlet is an effective learning medium for teaching ‘Adad Ma’dūd in Arabic. Therefore, it is recommended that teachers use Quizlet as an alternative learning medium, particularly for more complex Arabic materials, while still considering alignment with learning objectives.